TEKNIK ANALISIS SERPIH BILAH - Indah Asikin Nurani (Berkala Arkeologi, 2000)
In general, stone tool technology is based on two factors, namely methods and techniques. Method is in the form of mind, while technique is in the way we are practicing. The method of making tools is an order that is carried out systematically and regularly and is not something that happens by accident. The manner in which stone tools are made with the same technique and for hundreds of years has produced the same forms and technological features in various parts of the world.